Evolution of acceleration waves in non-ideal radiative magnetogasdynamics - Chaturvedi R.K.; Srivastava S.K.; Singh L.P. (My University, 2025)
In the present paper, the evolutionary behavior of weak shock waves propagating in an unsteady one-dimensional flow in non-ideal radiating gas under the effect of transverse magnetic field is examined. For the effect of thermal radiation, the radiative transfer equations are approximated under the optically thin limit. It is observed that a linear solution in the characteristic plane may exhibit a non-linear behavior in the physical plane. The transport equation governing the evolution of weak shock waves is obtained which introduces the conditions for shock formation. The time for the first breaking of the wave is determined. Also, the effect of radiative heat transfer on the growth of compressive waves and decay of expansive waves in ideal and non-ideal magnetogasdynamics regime is discussed. © 2019, Società Italiana di Fisica and Springer-Verlag GmbH Germany, part of Springer Nature.